KESALAHAN PENGGUNAAN EJAAN DALAM KARANGAN DESKRIPSI SISWA KELAS XI-9 SMA NEGERI 7 KUPANG - Mbuik, Ince; Nitbani, Semuel H.; Leda, Anastasia J. M (Jurnal Lazuardi, 2025)
ABSTRACT This study is entitled "Spelling Errors in Descriptive Essays of Grade XI9 Students of SMA Negeri 7 Kupang." This study aims to determine the form of spelling errors in the use of capital letters, comma punctuation, and the prefix di- and prepositions in descriptive essays of Grade XI-9 students of SMA Negeri 7 Kupang. The theory used in this study is the theory of language errors. The method used in this study is a descriptive qualitative method. Data collection techniques in this study were carried out using observation, testing, and documentation techniques. The results of the study stated that students still made many errors in the use of capital letters, comma punctuation, and the preposition di and the prefix di-. Errors in the use of capital letters were seen in the writing of the beginning of sentences, proper names, place names, regional names, and titles which often did not comply with the rules, some were even used excessively. Keywords: Errors, Spelling, Descriptive Essay